Desarrollo de modelos con técnicas de aprendizaje automatizado enfocados en el crecimiento y obtención de nuevos clientes para una empresa fintech en Colombia (2020)
The Fintech market has had a significant boom in recent years. One of the great tools that are being used to solve problems in these types of companies are machine learning algorithms, given the large amount of data and the positive results it has had in different industries. In this thesis, we seek to define in advance whether or not a potential user of an investment application will become a client. Likewise, we want to characterize the identified clients, this in order to define more robust and personalized marketing and sales strategies. With this in mind, the problem was divided into two parts, first, a classification task with machine learning was carried out in order to know whether or not a user will become a customer. Second, it was necessary to segment and characterize the company's customers...